A review of laser-induced breakdown spectroscopy signal enhancement. Issue 1 (2nd January 2018) - Li, Yingchao; Tian, Di; Ding, Yu; Yang, Guang; Liu, Ke; Wang, Chenghao; Han, Xu
ABSTRACT: A review of the methods of signal enhancement in laser-induced breakdown spectroscopy (LIBS) is presented. Conventional LIBS suffers from disadvantages of low sensitivity and high limits of detection compared with other analytical techniques, such as inductively coupled plasma mass spectrometry. During the last two decades, various methods have been applied to LIBS in order to realize highly quantitative and qualitative analysis. Current approaches include double-pulse excitation, spatial or magnetic confinement, spark discharge, etc. Different configurations of experimental setups and conditions are suggested for the realization of these improved techniques, while various parameters influence significantly on the enhancement effect. With the aim to study the laser ablation process and characterize the effectiveness of each method, several parameters such as plasma volume and emission intensity are reviewed. Several suggestions are proposed to explain the mechanism of each enhancement method. These modified techniques have been applied on various materials and fields.